Способ определения содержания в почве фосфора и гумуса - Рихванов Л. П. Леонид Петрович; Сарнаев С. И. Сергей Иванович; Балабаева Л. М. Людмила Михайловна; Ермохин А. И. Александр Иванович
опубл. 30.12.92